Microfluidic-Enabled Self-Directed Hydrogel Microspheres for Multiplexed MicroRNA Assays - Lin, Yongning; Xing, Gaowa; Wu, Zengnan; Lin, Jin-Ming; Lin, Jiaxu; Hou, Ying; Zheng, Yajing; Xu, Yan; Lin, Ling (Analytical chemistry (Washington), 2025)
Multiplexed microRNA (miRNA) detection has proven valuable in disease diagnosis; yet, the development of advanced tools for their analysis remains a subject of broad interest. Here, we propose a novel single-particle method for multiplexed miRNA detection using self-directed hydrogel microspheres, which feature supersegmented compartments for loading analyte probes and an air-encapsulated region that grants the microsphere a unique preferred posture in aqueous solutions. By exploiting microfluidic technology, we can widely adjust the size of the microspheres and the number of compartments can be widely adjusted. The air-encapsulated region is located at the edge of the microsphere’s symmetry axis, resulting in a spontaneous orientation that facilitates efficient multitarget signal readout in a standard manner without requiring active energy input. The microspheres exhibit excellent temperature stability, ensuring consistent performance under varying thermal conditions. Additionally, signal amplification strategies, such as hybridization chain reaction, are compatible with microspheres, enabling sensitive miRNA quantification. As a concept of proof, precise miRNA detection was demonstrated using these features. We hope that the proposed biocompatible microsphere tools will find broader application prospects in various clinical diagnostic settings.